Energy storage device electrodes and methods for producing dry energy storage device electrode films
By using ultrafibrosis binder particles and dry carbon particles in the electrode materials of energy storage devices, a high-strength and low-weight dry electrode film is formed, which solves the problem of difficult to take into account both the mechanical strength and thinness of the electrode materials in the prior art, and improves the electrochemical performance and mechanical performance.
Patent Information
- Application Number
- JP2024224725
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-03-01
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2037-02-27
AI Technical Summary
The electrode materials of existing energy storage devices are difficult to maintain sufficient mechanical strength and thinness while improving electrochemical properties, resulting in limited equipment performance.
The ultrafibrosis binding agent particles and dry carbon particles are used to form a high-strength, low-weight dry electrode film through ultrafibrosis treatment, and a conductive carbon material is used to reduce the equivalent series of resistance.
The high strength and low thickness of the electrode film are achieved, the electrochemical and mechanical properties of the energy storage equipment are improved, and the equivalent series resistance is reduced, and the energy density and power density of the equipment are improved.
Smart Images

Figure 2025060749000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an energy storage device, and in particular to a composition and a method for producing an electrode for an energy storage device. and a manufacturing method. [Background technology]
[0002] Many different types of energy storage devices can be used to power electrical devices. Such electrical devices include, for example, capacitors, batteries, and capacitor-balancers. Lithium-ion capacitors and hybrid and / or fuel cells. Any energy storage device can improve the composition of its electrodes to improve the electrical performance of the capacitor. It can be improved. Summary of the Invention
[0003] To summarize the present invention and the advantages it provides over the prior art, Certain objects and advantages are described herein. Not all such objects or advantages are necessarily specific. This is not achieved by any particular embodiment. The present invention relates to a method for achieving or optimizing one or more of the advantages or group of advantages described herein. It is to be understood that the invention is not to be construed as limiting the present invention without necessarily achieving any of the objects or advantages stated or implied. It will be understood that the present invention can be implemented or practiced in various ways.
[0004] In a first embodiment, a dry carbon particle, a dry superfibrillated binder particle, and a current collector are provided. and a free-standing dry electrode film, Poles are provided.
[0005] In one embodiment of the first aspect, the dry electrode film has a thickness of about 50 μm to about 120 μm. In one embodiment of the first aspect, the electrode is an anode. In one embodiment, the free-standing dry electrode film further comprises conductive carbon. In one embodiment of the aspect, the electrode film comprises about 1% by weight to about 5% by weight of conductive carbon. In one embodiment of the first aspect, the electrode comprises an electrolyte comprising a lithium salt. In one embodiment of the first aspect, the electrolyte is further in ionic contact with the cathode. In one embodiment of the first aspect, the dried ultrafibrillated biomass is in ionic contact with the The ethylenediamine particles constitute about 3% to about 7% by weight of the free-standing dry electrode film. In one embodiment of the present invention, a lithium ion capacitor is provided that includes an electrode.
[0006] In a second embodiment, dried carbon particles and dried fibrillizable binder particles are forming a first dry electrode mix containing a biphenyl and a biphenyl in the dry electrode mix; The DA was then superfibrillated to form a superfibrillated matrix in the electrode film mixture. forming a nanofibrillated electrode film mixture; and calendering the nanofibrillated electrode film mixture; forming a free-standing superfibrillated electrode film.
[0007] In one embodiment of the second aspect, the method is substantially free of processing additives. In one embodiment of the second aspect, the method includes the step of forming a free-standing electrode film. The method further includes contacting the first electrode with a current collector. In one embodiment, the method includes forming a second electrode and providing a separator between the first electrode and the second electrode. In one embodiment of the second aspect, the first electrode is an anode. In one embodiment of the second aspect, the free-standing dry electrode film is about 50 μm to about In one embodiment of the second aspect, the dried superfibrillated binder has a thickness of 120 μm. The particles contain about 3% to about 7% by weight of the superfibrillated matrix. In one embodiment, the step of forming the first mixture comprises adding conductive carbon particles to the first mixture. In one embodiment of the second aspect, the first mixture further comprises adding The conductive carbon particles are contained in an amount of about 1% by weight to about 5% by weight. The process of superfibrillating the binder is carried out by fibrillating the binder in the dry electrode film mixture. fibrillating the first fibrillated matrix to form a first fibrillated matrix; The process involves breaking down the binder particles to form a powder mixture of carbon particles and fibrillated binder particles. and fibrillating the powder mixture to obtain a second powder having the superfibrillated matrix. forming a fibrillated matrix.
[0008] The specification contains at least one color drawing, copies of which are included in the claims and are hereby incorporated by reference. and the necessary fees.
[0009] Other features, aspects, and advantages disclosed herein may be provided with reference to specific embodiments. The drawings are intended to illustrate specific embodiments. and is not intended to limit the present invention. [Brief description of the drawings]
[0010] [Figure 1]FIG. 1 is a side cross-sectional view illustrating a schematic example of an energy storage device according to an embodiment. [Diagram 2] FIG. 2 is a flow diagram showing an example of steps in a method for producing an electrode film. [Diagram 3] 1 is a table showing the equivalent series resistance performance of each of lithium ion capacitor cells having anodes with different types of conductivity-promoting additives. [Figure 4] FIG. 1 is a flow diagram showing an example of a method for manufacturing a thin electrode film. [Figure 5A] FIG. 2 is a schematic diagram of a payout machine for a calender line of an electrode film. [Figure 5B] FIG. 5B is a detailed view of a portion of the dispenser shown in FIG. 5A. [Figure 6A] 1 shows an SEM image of an electrode film prepared by prior art dry electrode processing. [Figure 6B] FIG. 1 shows SEM images of electrode films prepared by dry electrode processing using an ultrafibrillating binder. [Figure 7] 1 is a table showing data for various embodiments of lithium ion capacitors having anodes made by the methods provided herein.
[0011] Although specific embodiments and examples are described below, those of ordinary skill in the art will appreciate that the present invention may be practiced in Beyond the disclosed embodiments and / or uses, obvious modifications and equivalents thereof It will be understood that the scope of the invention disclosed herein is therefore limited to the following: The present invention should not be limited by the specific embodiments described.
[0012] In some embodiments, lithium ion batteries having improved electrical and / or mechanical performance are In some embodiments, an energy storage device such as a lithium ion capacitor (LiC) is provided. In some embodiments, the device may include an electrode that includes the improved electrode film composition. , which can provide improved electrical and / or mechanical performance. In some embodiments, the electrodes can be anodes and / or cathodes.
[0013] The disclosed embodiments provide enhanced fibrillation of binder materials compared to conventional methods; That is, the electrode film material undergoes "superfibrillation" as defined and explained herein. The present invention can include compositions, electrode films, electrodes, energy storage devices, and related methods. Many of the benefits in electrical and / or mechanical performance are due to enhanced fibrillation of the binder. This can be achieved by:
[0014] For example, by enhancing the fibrillation of the binder, the adhesion and flexibility of the binder can be improved. Such an embodiment may be equivalent to a fibrillated one. Uses the same or less amount of binder than comparable films that have no binder This can allow for the production of thinner films. Due to the self-supporting nature of dry electrode films and other reasons, wet electrode processing has traditionally been used. This could be beneficial for dry electrode film technologies, which tend to produce thicker films than conventional electrode film techniques. In addition, the proportion of binder in the electrode film relative to some of the other materials, such as conductive materials, Lower weight percentages ("binder loading") have advantages in electrical performance For example, the use of ultrafibrillated binders and the use of binders in electrode films The reduced amount of fluoride also results in a better performance than conventional films with conventional fibrillating binders. In comparison, it reduces undesirable electrical series resistance (ESR) in devices using the film. It is possible.
[0015] In some embodiments, the anode and / or cathode electrode films are made of fiber. The electrode may contain other electrode materials such as a disintegratable binder material and carbon. Polarized films allow for a reduction in the amount of binder material while maintaining desirable mechanical properties. Such desirable mechanical properties are of great value, for example, in the manufacture of energy storage devices. This may be related to the mechanical properties required for one or more processes. For example, in a dry manufacturing process When manufacturing electrodes by Advantageously, the present invention provides sufficient stability for rolling, handling, and other handling. Furthermore, by enhancing the fibrillation of the binder material, the calender line This can advantageously facilitate the formation of thinner electrode films capable of withstanding tensions of In some embodiments, increased numbers of fibrils, greater fibril surface area, and Electrode films containing longer and / or longer fibrils may be desirable during the manufacture of the film. Reduce the thickness while still exhibiting sufficient mechanical strength to maintain the integrity of the film It is possible.
[0016] The method for manufacturing the electrode film is different from the conventional electrode film fibrillation process. The processing speed is slowed down so that the fibrillation of the binder material can be enhanced. and / or a fibrillation process with increased processing pressure. For example, Enhanced fibrillation results in an increase in the number of fibrils, an increase in the fibril surface area, and / or Alternatively, longer fibrils from the binder material can be obtained, and the fibrils of conventional electrode films can be Uses less binder material compared to chemical treatment processes while still maintaining desirable mechanical properties Such an increase in the number of fibrils, an increase in the surface area of the fibrils, and / or Alternatively, longer fibrils may result in more effective matrix formation in the electrode film. This allows a structure to be constructed that provides one or more of the advantages set forth herein. In some embodiments, this more effective matrix structure is Increased tensile strength, shear stress and compression along the length compared to previous dry electrode technologies Resistance to stress and / or torsional stress, reduction in film thickness, increase in film density In certain embodiments, the electrode film may include any of the methods described herein. This is a free-standing electrode film with a reduced binder content so that it can be easily mounted on a substrate.
[0017] In certain embodiments, the electrode film comprises ultrafibrillated binder particles and carbon particles. The ultrafibrillated binder particles are processed in a process 200 and a process 202 for producing a self-supporting electrode film. and / or 400, and / or 401, which are binder particles produced according to the methods of production set forth herein. The binder particles are fibrillated, reduced in size, and then refibrillated. This allows for higher pressures, slower speeds, and slower feed rates than traditional fibrillation techniques. and / or binder particles that undergo fibrillation over a longer period of time. The fibrillated binder particles are characterized by the number of fibrils, the surface area of the fibrils, and / or the fibril size. The rills can be structurally defined based on their length, all of which are compatible with conventional binder fillers. The ultrafibrillated matrix presented here increases the surface area of the electrode. The structure formed by the components of the film mixture is the binder, which is formed by the fibrillation process. The nanoparticles are hyperfibrillated to the point where they stick together, as shown in Figure 6B. The structure is such that it is not compressed and is not made into an electrode film.
[0018] In some embodiments, the superfibrillated binder particles have a maximum dimension of about 3 μm. (microns), less than about 2 μm, less than about 1 μm, less than about 0.5 μm, less than about 0.3 μm, less than about 0.1 μm less than about 0.05 μm, less than about 0.03 μm, less than about 0.01 μm, or any value therebetween, e.g., Approximately 0.01 to 3 μm, approximately 0.03 to 2 μm, approximately 0.05 to 1 μm, or approximately 0.1 μm to 0.3 μm In yet another embodiment, the superfibrillated matrix is carbon particles, the carbon particles being at least 10%, at least 20%, at least 30%, At least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least at least 90%, at least 95%, or at least 99% of the surface area, or any range therebetween In some embodiments, the superfibrillated binder particles contact the binder particles at a surface area in the range of 0.1 to 1.0 mm. Indium particles are compared to conventional dry-processed electrode films with the same binder mass. Therefore, the number of ions present in the electrode film is at least twice as high.
[0019] Dry particle electrodes manufactured using standard techniques with conventional fibrillating binders Conventional dry electrode films made from film mixtures by dry processing are generally The anode is characterized by having a thickness of about 120 μm or more, and the cathode is characterized by having a thickness of about 120 μm or more. The thickness of the sintered body is approximately 80 μm or more. The reason for the difference in the thickness of the dry electrodes is that the anode electrode film is thicker than the cathode electrode film. This is because, at least in part, It is difficult to compress the carbon material of the anode compared to the activated carbon of the cathode electrode film. Generally, such conventional cathode films have a thickness of about 80 μm to about 10,000 μm. The thickness of the anode film may range from about 120 μm to about 10,000 μm.
[0020] In some embodiments, the fibrillation of the binder material is enhanced over conventional dry electrode processes. By strengthening the electrode film, it is possible to facilitate the formation of thinner electrode films. In addition, a thinner electrode film can reduce the volume it occupies and be used in a lithium-ion capacitor. In some embodiments, the superfibrillation of the binder material can be achieved by conventional fibrillation. The structural integrity of other similar conventional dry electrode films having fibrillated dry binder materials is Approximately 80 μm, 60 μm, or 50 μm or less while maintaining integrity and / or electrical performance This can facilitate the formation of a cathode electrode film having a thickness. In one embodiment, the electrode film produced by one or more of the process steps described herein has a thickness of about 120 μm. The electrode may have a thickness of about 50 μm or less, optionally including a thickness of about 80 μm, 60 μm, or even less than about 50 μm. In some embodiments, the enhanced fibrillation of the binder material is It may be easier to form an anode electrode film with a thickness of less than 120 μm. In an embodiment, by enhancing the fibrillation of the binder material, it is possible to obtain a thickness of, for example, 120 μm. Thin electrode fillers such as less than 80μm, less than 60μm, less than 50μm, less than 40μm, less than 30μm For example, the manufacture of anode electrode films having a thickness of less than 120 μm or less, Thinner electrodes, such as cathode electrode films with thicknesses of less than 120 μm, less than 80 μm, or thinner, In some embodiments, thinner electrode films can be manufactured more easily. The film can provide a lithium ion capacitor with improved power performance. In some embodiments, the anodes used in lithium ion capacitors have a thickness of about 40 μm to about Approximately 120μm, approximately 50μm to approximately 120μm, approximately 50μm to approximately 80μm, approximately 60μm to approximately 100μm, approximately 80μm to approximately 120 In some embodiments, the lithium ion catalyst comprises an electrode film having a thickness of 1 μm. The cathodes used in the capacitors are about 40 μm to about 80 μm, about 40 μm to about 70 μm, and about 50 μm to about 8 The electrode film has a thickness of about 50 μm to about 70 μm.
[0021] In some embodiments, the electrode film is conductive to facilitate lowering the equivalent series resistance. The additive contains a performance enhancing additive, which is carbon black and / or graphite. In some embodiments, the electrode film may be different from a conventional electrode film. In comparison, the amount of binder material is smaller and the amount of one or more conductivity-enhancing additives is larger, and therefore Therefore, the electrode film according to the embodiment has an equivalent series resistance while maintaining desirable mechanical properties. Indicates a drop in resistance.
[0022] A lithium ion battery comprising one or more electrodes containing the electrode film composition described herein. The silicon capacitor advantageously exhibits a reduced equivalent series resistance, which makes it more cost-effective than conventional electrode films. In some embodiments, the improved capacitor provides a higher power density compared to the conventional capacitor. The valence series resistance reduces heat generation, thereby improving the lithium-ion catalyst performance compared to conventional electrode films. In some embodiments, the capacitors described herein reduce or avoid heat dissipation. Lithium ion capacitors comprising one or more electrodes containing the electrode film composition are more In some embodiments, one or more of the electrodes described herein may be used. The lithium ion capacitors containing the electrode compositions may be prismatic, cylindrical and / or boron-based. In some embodiments, the encapsulation method described herein may have a variety of shapes, including a tongue shape. Lithium-ion capacitors with the electrolyte are used in hybrid electric vehicles (HEVs), powertrains, and power grids. Powering plug-in hybrid electric vehicles (PHEVs) and / or electric vehicles (EVs) It can be used to provide
[0023] The electrodes and energy storage devices described herein are in the context of lithium ion capacitors. However, embodiments may include one or more ballasts, with or without lithium. Battery, capacitor, capacitor-battery hybrid, fuel cell, combination of these Any of a number of energy storage devices and systems, including, but not limited to, In some embodiments, the electrodes can be used in ultracapacitors, lithium ion batteries, cathode or cathodes configured for use in lithium-ion batteries or lithium-ion In a preferred embodiment, the electrode is for use in a lithium ion capacitor. The anode is configured to
[0024] FIG. 1 is a schematic side cross-sectional view of an example of an energy storage device 100. 00 may be a lithium ion capacitor. Of course, other energy storage devices are also possible. Within the scope of the present invention, batteries, capacitor-battery hybrids, and / or It should be understood that the energy storage device 100 may include a fuel cell. 2, a second electrode 104, and a separator 106 disposed between the first electrode 102 and the second electrode 104. For example, the first electrode 102 and the second electrode 104 can be disposed on both sides of the separator 106. The first electrode 102 may be a cathode. , the second electrode 104 may be the anode, or vice versa (the first electrode 102 is the anode, The second electrode 104 may be a cathode. An electrolyte 122 may be provided to facilitate ionic transfer between the electrodes 102, 104 of the device 100. For example, the electrolyte 122 may be in contact with the first electrode 102 , the second electrode 104 , and the separator 106 . The electrolyte 122, the first electrode 102, the second electrode 104, and the separator 106 form the hub of the energy storage device. For example, the energy storage device housing 120 may be A first electrode 102, a second electrode 104, a separator 106 and an electrolyte 122 are introduced to form an energy storage device. After the electrolyte 122 is impregnated into the electrode 100, the first electrode 102, the second electrode 104, the separator 106 and the electrolyte The energy storage device 122 may be sealed such that it is physically sealed from the environment outside the housing. Although the gas storage device 100 is shown as a dual electrode, dual layer device, other configurations, such as a single layer electrode, may be used. It will be appreciated that other types of
[0025] The energy storage device 100 may include any of several different types of electrolytes 122. For example, the device 100 may include an electrolyte for a lithium ion capacitor. The electrolyte may include a lithium source, such as a lithium salt, and a solvent, such as an organic solvent. In some embodiments, the lithium salt is lithium hexafluorophosphate. Lithium (LiPF6), Lithium tetrafluoroborate (LiBF4), Lithium perchlorate (LiClO4) , lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), trifluoro Lithium sulfonate (LiSO3CF3), combinations thereof, and / or In some embodiments, the dissolution of the lithium ion capacitor electrolyte includes, for example, The catalyst may include one or more ethers and / or esters. For example, lithium The solvent for the electrolyte of the lithium ion capacitor is ethylene carbonate (EC), dimethyl carbonate (DMCO), etc. Diethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), vinyl propylene carbonate (VC), propylene carbonate (PC), combinations thereof, and / or or equivalents thereof. For example, the electrolyte may include LiPF6, ethylenediaminetetraacetate, The carbonates may include propylene carbonate, and diethyl carbonate.
[0026] The separator 106 has two electrodes adjacent to each other on opposite sides of the separator 106, for example, a first electrode 102 and the second electrode 104 are electrically isolated while allowing ionic transfer between the two adjacent electrodes. The separator 106 can be configured to allow for a variety of porous, electrically insulating In some embodiments, the separator 106 comprises a polymeric material. For example, the separator 106 can be made of a cellulose material (e.g., paper), polyethylene, Polyethylene (PE) materials, polypropylene (PP) materials, and / or polyethylene and polypropylene The material may include propylene.
[0027] As shown in FIG. 1, the first electrode 102 and the second electrode 104 are disposed between a first current collector 108 and a second current collector 110. The first current collector 108 and the second current collector 110 are connected to the corresponding electrodes and an external circuit (not shown). The first current collector 108 and / or the second current collector 109 may be easily electrically coupled to each other. The current collector 110 may contain one or more conductive materials and / or may be provided with a corresponding and a terminal for coupling the energy storage device 100 to an external circuit, such as an external electrical circuit. The electrodes can be of various shapes and sizes that facilitate the transfer of charge between the electrodes. The conductive material may be any material including aluminum, nickel, copper, silver, and alloys thereof. For example, the first current collector 108 and / or the second current collector 110 may be rectangular. The aluminum foil may be of a rectangular or substantially rectangular shape with corresponding electrodes and Transfer of desired charge to or from an external electrical circuit (e.g., current collector plates and / or electrodes via another component of the energy storage device configured to electrically couple to an external electrical circuit. The electrodes can be dimensioned to provide a dielectric constant (e.g., charge transfer) that is proportional to the distance between the electrodes.
[0028] The first electrode 102 is a first electrode 102 on a first surface of the first current collector 108 (e.g., the top surface of the first current collector 108). A film 112 (e.g., a top electrode film) and an opposing second surface (e.g., a second electrode film 114 (e.g., a lower electrode film) on the bottom surface of the first current collector 108) Similarly, the second electrode 104 is provided on a first surface of the second current collector 110 (e.g., a first electrode film 116 (e.g., a top electrode film) on the top surface of the second current collector 110 a second electrode film 118 on the opposing second surface (e.g., the bottom surface of the second current collector 110); For example, the first surface of the second current collector 110 faces the second surface of the first current collector 108. The separator 106 is a second electrode film 114 of the first electrode 102 and a first electrode film 114 of the second electrode 104. It is adjacent to Mu 116.
[0029] The electrode films 112, 114, 116 and / or 118 may be of any suitable shape, size, and / or shape. For example, the electrode film can be about 100 μm (microns) to about 25 The thickness of the insulating layer 110 can be from about 30 μm to about 250 μm, including 0 μm.
[0030] In some embodiments, an electrode film, such as electrode film 112, 114, 116, and / or 118, One or more of the films may contain a mixture that contains a binder material and carbon. In some embodiments, the electrode film may further comprise one or more additives, such as a conductivity enhancing additive. In some embodiments, the cathode of the lithium ion capacitor may contain The electrode film of the electrode contains one or more carbon-based electroactive components, such as porous carbon materials. In some embodiments, the electrode film may include a mixture of a cathode The porous carbon material includes activated carbon. For example, the cathode electrode film includes a binder material , activated carbon and conductivity promoting additives. In some embodiments, The anode electrode film of a lithium-ion capacitor reversibly transfers lithium ions The electrode film contains a mixture of carbon that is configured to be tarcalinized. In some embodiments, the lithium intercalating carbon is graphite. For example, the anode electrode film is made of binder material, graphite and conductive additives. It may contain an agent.
[0031] In some embodiments, the binder material comprises one or more fibrillizable binder components. For example, the process for forming the electrode film may include this fibrillating component. The binder component is fibrillated so that the electrode film contains the fibrillated binder. In some embodiments, the fibrillating binder can be The binder component comprises a superfibrillated binder particle having a plurality of fibrils. The fibrils may be fibrillated to separate one or more other components of the film. For example, a matrix of fibrils, a lattice and / or Alternatively, a web can be formed to provide a desired mechanical structure to the electrode film. For example, the cathode and / or anode of a lithium ion capacitor may be made of one or more ?lms. One or more electrode films may be provided that contain a brilly binder component. In some embodiments, the binder component is polytetrafluoroethylene (PTFE), an ultra-high molecular weight Polyethylene (UHMWPE), and / or other suitable fibrillizable materials, either alone or or a combination thereof.
[0032] In some embodiments, the electrode film has the same properties as conventional electrode films while maintaining desirable mechanical properties. In some embodiments, the binder material weight is less than that of known dry electrode films. The electrode film is about 1% by weight to about 10% by weight, about 3% by weight to about 15% by weight, about 3% by weight to about 10% by weight %, about 3% to about 8% by weight, about 3% to about 7% by weight, about 3% to about 6% by weight, or about In yet another embodiment, the electrode film comprises 3% to about 5% by weight of a binder material. , for example, about 5% by weight to about 6% by weight or about 6.5% by weight to about 8% by weight, about 4% by weight to about 7% by weight In some embodiments, the electrode film is an anode containing a binder material of about 7% to about 11% by weight, for example about 8% to about 10% by weight, of a binder material together with activated carbon. In some embodiments, an electrode film, such as an anode film, The composition may have a binder content of less than about 4% by weight or less than 3% by weight, for example, less than about 0.5% by weight. % to 4% by weight, 1% to 4% by weight, 0.5% to 3% by weight, or 1% to 3% by weight. In some embodiments, the electrode film with a low amount of binder is resistant to tension, shear, A desired resistance to compressive and / or torsional stresses can be maintained.
[0033] In some embodiments, the electrode film has a binder relative to other materials in the film. The lower amount of material allows for increased amounts of conductivity enhancing additives, improving electrical performance. For example, the anode according to such an embodiment may maintain desirable mechanical properties or In some embodiments, the equivalent series resistance can be improved while increasing To achieve the desired electrical performance, certain types of conductivity enhancing additives are included in the electrode film. For example, an electrode film with a low binder content has a low equivalent series resistance. while demonstrating improvements in tensile, shear, compressive and / or torsional stresses. , thereby outperforming other conventional energy storage devices of comparable construction. The power density of energy storage devices such as lithium-ion capacitors is higher than that of Manufacturing becomes easier.
[0034] In some embodiments, the conductivity enhancing additive comprises conductive carbon. In an embodiment, the conductive carbon is one or more of carbon black and / or graphite. In some embodiments, the one or more carbon blacks include commercially available {Shoyo}Ketjenblack (registered trademark) manufactured by Akzo Nobel NV, Im C-NERGY™ Super C65 from Imerys Graphite & Carbon, Ltd. , Ltd., Super P®, Cabot Corp., BP2000®, and / or and LITX® 50 manufactured by Cabot Corp. In some embodiments, one or more of the above may be used. The graphite was commercially available as ABG1010 and / or Superior Graphite Co. ABG1005 manufactured by Raphite Co., Ltd. For example, anode electrode film for lithium ion capacitors The film may contain one or more of the conductivity-promoting additives described herein. In some embodiments, the conductive carbon is about 1% by weight in the electrode film mixture. may be from about 1% to about 10% by weight, including from about 8% by weight, or from about 1% to about 5% by weight. In some embodiments, the electrode film may be made of a conductive carbon as described herein. By incorporating conductive carbon, the energy storage device can achieve approximately 5 times the energy consumption compared to an energy storage device that does not contain conductive carbon. % ESR improvement. In yet another embodiment, the conductive carbon has a surface area of 10 ~100m 2 / g, e.g. 20~50m 2 / g, and / or particle size of 0.1 to 10 μm. In yet another embodiment, the conductive carbon has a particle size of about 0.1 μm to about 0.5 μm. or about 10 μm. A lithium ion capacitor having an anode produced by the method has an ESR value of about 0.1 (m ohm) (milliohms) to about 10 (m ohms), for example, about 0.5 (m ohms) to about 5 (m ohms), or about 1.5 (m ohms) (m ohms) to approximately 3.5 (m ohms).
[0035] In some embodiments, one or more of the electrode films described herein are prepared using a dry process. In this specification, the dry manufacturing process is a process for manufacturing an electrode film. It can refer to a process in which no or substantially no solvent is used in the formation of the For example, the components of the electrode film can include dry particles. Dry particles for forming the electrode film can be mixed together to provide a dry particles electrode film mixture. In some embodiments, the electrode film comprises a dry particle size distribution determined by weight percentages of the components of the electrode film. Dry manufacturing processes were used to ensure that the weight percentages of the components in the electrode film mixture were similar. In some embodiments, the dry particle electrode film may be formed from a dry particle mixture. The electrode film formed from the dry particle electrode film mixture by the manufacturing process It may be free or substantially free of processing solvents and solvent residues resulting therefrom. In some embodiments, a dry particle electrode film mixture is fabricated using a dry manufacturing process. The resulting electrode film may be cleaner and / or structurally stronger. and thereby resulting in improved electrochemical and / or mechanical performance. In some embodiments, the electrode film is formed by dry processing from a dry particle mixture. In some embodiments, the free-standing dry particle electrode film is The film consists essentially of dry carbon particles and dry superfibrillated binder particles. In some embodiments, the fibrillating polymer may comprise or consist of a single fibrillating polymer such as PTFE. Only a single binder is needed to form a free-standing dry electrode film such as a binder that can be used Used.
[0036] In some embodiments, the energy storage device is not a battery.
[0037] FIG. 2 illustrates an example process 200 for manufacturing an electrode film, according to some embodiments. FIG. 2 is a flow diagram illustrating a process 200 for manufacturing an electrode film. is a dry processing process and the resulting electrode film is free of liquids, solvents and residues. In block 202, the carbon black is removed from the solution by removing the carbon black from the solution. An electrode film mixture is formed that includes the particles and a binder material. Optionally, one or more In some embodiments, the electrode filler may be mixed with the above conductivity enhancing additives. The powder mixture is a dry particle mixture. In some embodiments, the binder material is polytetrafluoroethylene. One or more of polytetrafluoroethylene (PTFE) and ultra-high molecular weight polyethylene (UHMWPE) In some embodiments, the binder material comprises a fibrillizable polymer of PTFE. In some embodiments, the polymer comprises, or consists essentially of, one such polymer. The conductivity enhancing additive can be one or more conductive carbons. For example, conductive carbons The composition may include one or more carbon blacks and / or graphites as described herein. This can be done.
[0038] In block 204, the binder in the electrode film mixture is ultrafibrillated to form ultrafibrillated The process of superfibrillation can form a fibrillated matrix. The polymerization can be carried out at a slower process speed and / or at a higher process pressure. For example, the process of superfibrillation is described in U.S. Patent Application Publication No. 2015 / 0072234. In some embodiments, the pressure can be reduced and / or reduced compared to the conventional method. In some embodiments, the superfibrillation process may be a mechanical shearing process. such that the material can be mechanically treated to form a plurality of fibrils from the binder material; The binder material may be subjected to mechanical shear forces. In some embodiments, The process of mechanical shearing includes mixing and / or milling. Particles of the rum mixture are provided to a blender and / or mill, and the blender and / or mill The rate at which the electrode filler is circulated through the mill may be reduced during the superfibrillation process. By slowing the rate at which the particles of the rubber mixture circulate through the blender and / or mill, The particles of the electrode film mixture are mixed in the process chamber of the blender and / or mill. In some embodiments, the time for the circulation can be increased. By increasing the time between the binders, the fibrillation of the binders is enhanced, resulting in the superfibrillation of the mixture. In some embodiments, the particles of the electrode film mixture may be blurred. The circulation speed in the render and / or mill is the speed at which the particles circulate once in the process chamber. The time for which the electrode is treated should be determined to be about 1.2 to 3 times longer than that of conventional dry electrode treatment. For example, the mixing and / or grinding process time for conventional dry processing is about 1 minute. In some embodiments, the mixing and / or grinding time may be about 2 minutes, about 3 minutes, or about 4 minutes. , about 4 minutes, about 5 minutes, about 7 minutes, or about 10 minutes. The mixing and / or grinding feed rate is Compared to conventional dry electrode processing, the speed can be reduced by about half. In an embodiment, the mixing and / or grinding feed rate is about 10% of the rated machine feed rate, constant Approximately 20% of the feed speed of the rated machine, Approximately 30% of the feed speed of the rated machine, Approximately 40% of the feed speed of the rated machine , about 50% of the rated machine feed speed, about 60% of the rated machine feed speed, about 70%, approximately 80% of the rated machine feed rate, or approximately 90% of the rated machine feed rate. In some embodiments, the electrode film is formed by drying the dry mixture of carbon particles and binder for about 2 minutes to about 5 minutes. The method is carried out by a process comprising mixing and / or grinding the mixture for 10 minutes. .
[0039] In some embodiments, a continuous mixing process can be performed. The mixing and / or grinding time may be inversely proportional to the feed rate. In such an embodiment, the conventional dry filler may be used to increase the mixing and / or grinding time. The feed rate can be reduced compared to the Brillization process. By reducing this feed rate by half, the mixing and / or grinding time is doubled. For example, the feed rate for conventional dry processing in a particular machine is about 50-60 kg / hr. Thus, in some embodiments, the superfibrillation provided herein may be The binder or matrix can be produced on the same machine with a feed rate of about 25-30 kg / hr. Generally, this feed rate will depend on the milling machine and will be discussed in detail herein. Based on the operating parameters of the machine, the amount of heat generated can be adjusted in accordance with the operating parameters of the machine. In the form of mixing and / or grinding, the use of larger channel equipment If a batch mixing and / or grinding process is used, the time can be increased. The processing time can be increased simply by mixing and / or grinding for a longer period of time. Cut.
[0040] In some embodiments, the process in the blender and / or mill during the fibrillation process The treatment pressure can be increased to effect superfibrillation. In some embodiments, the treatment pressure The greater the force, the greater the shear force applied to the binder material, which in turn causes the binder In some embodiments, the treatment pressure for superfibrillation is The shear force applied to the Inda material is the same as that in the fibrillation process of conventional dry electrodes. It can be determined to be about 1.2 to 3 times.
[0041] The superfibrillation process, which is carried out at a slow processing speed and / or high processing pressure, The fibrillation of the binder material is promoted, increasing the number of fibrils formed from the binder material, May promote increased fibril surface area and / or longer fibril lengths In some embodiments, slowing down the treatment speed and / or increasing the treatment pressure may be used. This enhances fibrillation and reduces tension, shear, and other stresses from a small amount of binder. To form an electrode film having a desired resistance to compressive and / or torsional stresses. For example, the treatment speed can be slowed down and / or the treatment pressure can be increased. This allows the amount of binder material to be reduced while still providing the desired amount of one or more other components of the film. It is possible to promote the formation of a sufficient amount of fibrils to provide mechanical support for the In some embodiments, the mixing step of block 202 and the fibrillation step of block 204 are carried out in a 1 The process may be one or substantially one continuous process.
[0042] In certain embodiments, the superfibrillation of block 204 is the same as a conventional fibrillation process. This can be done by repeating the process two or more times for the same material. The first fibrillation step can form a fibrillated matrix. This fibrillated matrix can then be reduced in size, e.g. A powder electrode film mixture may be formed. For example, block 204 may be formed by mixing the first fiber. The method may include the step of destroying the ionized electrode film mixture. The breaking process involves passing the fibrillated electrode film mixture through a strainer, a sifter, a mesh This may include passing the material through a shredder, riddle, screen and / or sieve. The resulting fibrillated electrode film mixture is then subjected to a second fibrillation step as described herein. This second fibrillation step may be referred to herein as a superfibrillation step. As shown, fibrillation steps performed at slow processing speeds and / or high processing pressures A second fibrillation step may result in a second powder electrode film mixture. The second powder electrode film mixture is then subjected to further steps in block 204. Alternatively, the process of block 206 may be performed. In this embodiment, a second (or additional) fibrillation step is performed to obtain an electrode filtrate with enhanced fibrillation. The present invention provides a method for producing a fluororesin mixture comprising the steps of: The superfibrillation of the binder in 04 can be performed by fibrillating it once, twice, three times or more. Finally, in block 204, the ultrafibrillation process shown herein can be carried out after the sub-steps. A fibrillated matrix and / or ultrafibrillated binder particles are obtained.
[0043] At block 206, the fibrillated electrode film mixture is calendered in a calendering apparatus. The calendering apparatus can be used to form free-standing superfibrillated electrode films. The electrode film composition is generally prepared by mixing the electrode film with the electrode film. In some embodiments, the electrode film is formed by calendering the electrode material through a pair of calender rolls. As further described herein, additional additives may be added to form a film with a desired minimum thickness. The electrode film is formed in the first calendaring process without an additional calendaring process. In some embodiments, the calendered mixture can be a liquid, a solvent, and a self-supporting dry particulate form free or substantially free of residues resulting therefrom. In some embodiments, the electrode film is an anodic electrode film. In some embodiments, the electrode film is a cathodic electrode film. In some embodiments, the superfibrillated electrode film mixture is calendered under selected conditions. For example, in still another embodiment, the calendering may be performed for 10 to 30 minutes. It can be done at a temperature of 0°C and a pressure of 5 to 150 kilonewtons. They may be of any size selected for the application, but generally range in diameter from 5 to 80 cm. This is also fine. EXAMPLES
[0044] FIG. 3 shows a lithium-ion battery with an anode containing different types of conductivity-promoting additives. 1 is a table showing the equivalent series resistance of each of the capacitor cells. The type of conductivity-promoting additive contained in the node and the corresponding equivalent series resistance determine the conductivity-promoting additive. The percentage improvement is shown over a lithium-ion capacitor without additives. The conductivity-enhancing additives tested were mesoporous carbon and various types As shown in Figure 3, the conductive carbon contained a specific type of conductive carbon. Lithium ion capacitors with anodes having the same properties exhibit improved equivalent series resistance performance. However, lithium ion capacitors with anodes containing mesoporous carbon have an equivalent Did not show any noticeable improvement in series resistance. For example, Lithium-ion capacitors with anodes that have an equivalent series resistance of 5% or more showed improvement.
[0045] Also, metal powders such as silver (Ag) powder, nickel (Ni) powder, or copper (Cu) powder are included. Lithium-ion capacitors with anodes made of ZnO showed significant improvement in equivalent series resistance. I didn't.
[0046] FIG. 4 illustrates a process 400 for manufacturing a thin electrode film, according to some embodiments. 1 is a flow diagram showing an example of a method for manufacturing a cathode electrode film. In some embodiments, the electrode film can be an anode electrode. In some embodiments, the electrode film can be a film. Step 400 is a dry process, does not use liquids or solvents, and the resulting electrode film is Free or substantially free of liquids, solvents and their residues. In one embodiment, step 400 is performed to generate a charge for an ultracapacitor, a battery, and / or a lithium An electrode of an ionic capacitor can be formed.
[0047] At block 402, an electrode film containing a binder material and one or more conductivity-promoting additives is formed. The components of the film mixture can be mixed together. In some embodiments, the electrode film The rubber mixture is a dry particle mixture. The binder is polytetrafluoroethylene (PTFE). and one or more fibrillizable polymers, such as ultra-high molecular weight polyethylene (UHMWPE). In some embodiments, the binder material may include one type of binder, such as PTFE. In some embodiments, the conductivity-promoting additive comprises a polymer. For example, the conductive carbon may be one or more of the conductive carbons described herein. It may contain one or more types of carbon black and / or graphite.
[0048] At block 404, the electrode film mixture is mixed with the binder material to form fibrils. The fibrillation process can be slow and / or The process can be carried out at high processing pressures. The pressure can cause tension, shear, compression and / or twisting forces to form from a small amount of binder material. In order to form an electrode film having a desired resistance to stress, As described herein, in some embodiments, The fibrillation process may be a mechanical shearing process, such as a mixing process and / or a grinding process. In some embodiments, the electrode film mixture may be added during the fibrillation process. The rate at which the particles of the mixture circulate through the blender and / or mill can be slowed. In some embodiments, the internal process of the blender and / or mill during the fibrillation process In some embodiments, the mixing step of block 402 and the processing pressure can be increased. and the fibrillation step of block 404 may be one or substantially one continuous step. Slower processing speeds and / or higher processing pressures may result in the above-mentioned larger Electrode films having a high strength, e.g., less than 120 μm or as previously described herein, Thinner than previously possible, in a single high pressure calendering step (single step) or multiple After the first calendering step, the film is unwound. and then recalendering one or more times.
[0049] In certain embodiments, block 404 may include, as described with reference to block 204 of FIG. The size of the fibrillated electrode film mixture can be reduced, for example, by breaking it. In block 406, the method may include reducing and refibrillating the fiber. Calendaring the fibrillated electrode film mixture to form a first electrode film. In block 408, the first electrode film can be unwound. For example, The first electrode film is fed through a payout machine as shown in FIGS. 5A and 5B, which will be described below. In block 410, the unwound electrode film is rewound at least once. In some embodiments, the electrode film can be about 50 μm or less. To form a thin electrode film, such as a thickness or other thicknesses described herein. In some embodiments, the thin electrode can be recalendered two or more times. The film may be provided with the desired resistance to tensile, shear, compressive and / or torsional stresses. For example, the calender line is drawn once. The thickness of the electrode film, such as the anode electrode film of a lithium-ion capacitor, that has been passed through The diameter of the fiber may be about 120 μm. The electrode film is made of high strength, calendered electrode film that is rolled out to a thickness of approximately 120 μm. One or more additional passes can be made through the calender line to reach a thickness of less than 100 mm. For example, the film may be calendered a second time to a thickness of, for example, about 80 μm or less. The recalendered anode electrode film can be unwound. After passing through the calendar line for the third time, an electrode film with a thickness of about 50 μm is obtained. can.
[0050] In some embodiments, the electrode film is less than 80 μm thick, or a conventional electrode film. Other electrode films described herein that are thinner than the cellulose acylate film are made of ultrafibrillated binders. The electrode film mixture with the da is produced by passing it through the calendar line only once. For example, calendaring can enhance the fibrillation of fibers due to its enhanced fibrillation. Due to the high strength of the film, the mixture can be calendered only once to a thickness of less than 80 μm. This can be done by exerting sufficient pressure on the electrode film mixture so that a high thickness can be achieved. The electrode film mixture is processed once in a calendaring apparatus to obtain a desired electrode film. Reducing the desired thickness can provide cheaper and / or faster manufacturing processes. This can be done.
[0051] FIG. 5A is a schematic diagram of one embodiment of a payout machine for a calender line of an electrode film. FIG. 5B is a more detailed view of a portion of the dispenser shown in FIG. 5A. The apparatus shown can be used to perform the recaldern process step 410 of FIG. For example, in the illustrated embodiment, a free-standing dry electrode film (shown as a "feeding material" in FIG. 5B) is The yarn is then unwound and recalendered by a pair of rollers as shown. A calendering device similar to the rollers shown in Figures 5A and 5B may also be used to calender the dried electrode mixture. 2 and 410 of FIG. 4 or other embodiments. The first calendering step allows the initial formation of a free-standing dry electrode film. It will be understood that this is possible.
[0052] Figures 6A and 6B show SEM images of the dry electrode film matrix. SEM images of the dry electrode film matrix produced by conventional dry electrode processing are shown. FIG. 6B shows a graph of the nanofibrillation process prepared according to step 200 or other ultrafibrillation processes described herein. The dry electrode film matrix shown in FIG. 6A shows the electrode film with 8% binder. The electrode film in FIG. 6B contains 6.5% binder and has a thickness of 50 μm. The electrode film in FIG. 6B is an electrode film mixture that has been milled twice. As can be seen from a comparison of Figures 6A and 6B, the dry electrode film in Figure 6B The matrix is characterized by enhanced fibrillation of the binder. In contrast, in FIG. 6B, the number of fibrils increases. In FIG. 6A, the carbon particles (shown in the figure) In FIG. 6B, a substantial portion of the carbon particles (which are not shown) have free surfaces, and in FIG. Generally, the binder shown in FIG. 6B has the same quality and coverage as the binder shown in FIG. 6A and has a larger surface area to contact the carbon particles. The binder in Figure 6B is an example of a superfibrillated binder provided herein.
[0053] FIG. 7 illustrates various embodiments of an anode made by the methods described herein. Regarding the lithium ion capacitor, the binder content, the film thickness, the capacitance The amount, and ESR are shown.
[0054] Although the present invention has been disclosed in the context of specific embodiments and examples, those skilled in the art will appreciate that The invention may be practiced in other embodiments and / or other uses of the invention beyond the specifically disclosed embodiment. In addition, it will be understood that the present invention is applicable to various uses, modifications, and variations. Although certain variations have been shown and described in detail, other modifications which are within the scope of the invention are within the spirit and scope of the present disclosure. Certain features and aspects of these embodiments will be readily apparent to those of ordinary skill in the art based on the disclosure. It is understood that various combinations or subcombinations of the above may be made and are within the scope of the present invention. It should be understood that various features and aspects of the disclosed embodiments are within the scope of the present invention. or may be combined with one another to form various other aspects of the disclosed embodiments of the invention. It should be understood that the terms can be substituted for one another. The scope of the present invention should not be limited by the specific embodiments described above.
[0055] The headings used herein are for convenience only and do not limit the scope of the invention as disclosed herein. It does not necessarily affect the scope or meaning of the apparatus and methods used.
Claims
1. A free-standing dry binder material comprising dry carbon particles and dry ultrafibrillated binder particles. An electrode film; Current collector and An electrode for an energy storage device comprising:
2. The dry electrode film has a thickness of about 50 μm to about 120 μm.
2. The electrode according to claim 1.
3. Anode 2. The electrode according to claim 1.
4. The free-standing dry electrode film further contains conductive carbon.
2. The electrode according to claim 1.
5. The electrode film contains about 1% to about 5% by weight of conductive carbon.
2. The electrode according to claim 1.
6. It is in ionic contact with an electrolyte containing a lithium salt 2. The electrode according to claim 1.
7. The electrolyte is in ionic contact with the cathode.
6. An electrode as claimed in claim 5.
8. The dried superfibrillated binder particles comprise about 5% by weight of the free-standing dry electrode film. % to about 7% by weight 2. The electrode according to claim 1.
9. A lithium ion capacitor comprising the electrode according to claim 1.
10. A method for producing a dry electrode film for an energy storage device, comprising: A first dried mixture containing dried carbon particles and dried fibrillizable binder particles. forming a dry electrode mix; The binder in the dried electrode film mixture is ultrafibrillated to form the electrode film mixture. forming an ultrafibrillated matrix in the article; The superfibrillated electrode film mixture was calendered to form free-standing superfibrils. forming a photosensitive electrode film; A manufacturing method comprising:
11. It is a dry process that uses virtually no processing additives. The method according to claim 10.
12. Contacting the free-standing electrode film with a current collector to form a first electrode. Also includes The method according to claim 10.
13. forming a second electrode; inserting a separator between the first electrode and the second electrode; Also includes 13. The method of claim 12.
14. The first electrode is an anode.
13. The method of claim 12.
15. The calendering process compresses the free-standing dry electrode film to a thickness of about 50 μm. 1.0 to about 120 μm The method according to claim 10.
16. The above step of calendering to a thickness of about 50 μm to about 120 μm is a single calendering step. Consists of 16. The method of claim 15.
17. The dried superfibrillated binder particles may comprise from about 5% to about 7% by weight of the superfibrillated binder particles. Contains matrix The method according to claim 10.
18. The step of forming a first mixture includes adding conductive carbon particles to the first mixture. Further including The method according to claim 10.
19. The first mixture contains about 1% to about 5% by weight of the conductive carbon particles.
20. The method of claim 18.
20. The manufacturing method according to claim 10, The above process of superfibrillating the binder comprises: The binder in the dried electrode film mixture is fibrillated to form a first fibrillated matrix. forming a rix; Destroying the first fibrillated matrix to release the carbon particles and the fibrillated binder particles. forming a powder mixture of The powder mixture is fibrillated to form a second fiber comprising the superfibrillated matrix. forming a fibrillated matrix; A manufacturing method comprising:
Citation Information
Patent Citations
Dry particle-based electrochemical device and method for manufacturing the same
JP2007531245A
Method of manufacturing electrode composite for secondary battery, electrode for secondary battery and secondary battery
JP2011258333A
Electrode for electrochemical element
JP2013077558A
Nonaqueous electrolyte secondary battery
JP2015146249A